Sensor óptico baseado em fibra óptica de núcleo vazado e curvatura negativa para detecção simultânea de metano, monóxido de carbono e monóxido de nitrogênio - Silva, Artur Araujo (Universidade Federal de São Carlos, 2019)
This work demonstrates the potential for application of negative curvature hollow core fibers (HC-NCF) as efficient sensors to monitor three gases simultaneously, methane (CH4), carbon monoxide (CO) and nitrogen monoxide (NO). With the insertion of lateral holes in these fibers, the ambient gas can enter the hollow core, causing the light that propagates in the fiber to interact with this gas. This interaction between light and gas, in spectral regions where the gases present high absorption, allows the monitoring of low concentrations of gases present in the environment, by attenuating the light output. The results of the simulations show a linear behavior of the loss as a function of the gas concentration for the three gases of interest. This linearity between the propagation losses and the variation of the concentrations of gases in the environment can promote its application in the area of ​​health and the environment, to monitor low concentrations of gases with high speed and precision.
Optical sensor based on negative curvature hollow core optical fiber for simultaneous detection of methane, carbon monoxide and nitrogen monoxide
Keywords: Fibras ópticas; Sensores ópticos; Sensores a fibras ópticas; Fibras ópticas microestruturadas; Fibras ópticas com núcleo de curvatura negativa; ENGENHARIAS::ENGENHARIA ELETRICA